DETERMINANT FACTORS OF MSME FINANCING IN ISLAMIC BANK (STUDY CASE IN INDONESIA) - irena Paramita Pramono; Rudy Hartanto; Tria Apriliana (AKUNTANSI DEWANTARA, 2019)
Micro, Small and Medium Enterprise (MSME) is an important segment of the Indonesian economy. The amount of MSME in Indonesia is 99,9% of the total entrepreneurs, it has high employment absorption and has a big contribution to the GDP. Despite the importance of MSME in Indonesia, financing, and lack of information become the main problem in MSMEs growth. In addition to financial assistance, Indonesia's MSMEs also need partner and guidance to help them grow. Islamic bank is an important segment in Indonesia's banking industry. We believe with a good coherency within Islamic Bank and MSME, both can support each other better either in financial aspect and management aspect. Therefore this research try to give an understanding what is the determinant factors of Islamic Bank financing for MSME, either in bank umum syariah and unit usaha syariah. This research use time series data of Islamic Bank financing, which monthly released by Otoritas Jasa Keuangan. There are several factors examined in this paper, which are Net Performing Financing (NPF), Return On Financing (ROA), Third Party Funds or Dana Pihak Ketiga (DPK), number of offices, number of workers and policy rate.